Focal Choroidal Excavation - Zafer Cebeci; Şerife Bayraktar; Merih Oray; Nur Kır (Türk Oftalmoloji Dergisi, 2016)
Focal choroidal excavation is a choroidal pit that can be detected by optical coherence tomography. Central serous chorioretinopathy, choroidal neovascularization and polypoidal choroidal vasculopathy are pathologies associated with focal choroidal excavation. In this article, we present the follow-up and treatment outcomes of three eyes of two patients with focal choroidal excavation.